PENGARUH WAKTU DAN TEMPERATUR HIDROTERMAL TERHADAP HASIL UJI XRD HIDROKSIAPATIT DARI CANGKANG KERANG ALE-ALE - AGUSTO BRIA SERAN; Erich U. K. Maliwemu; Dominggus G. H. Adoe (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
This study aims to analyze the changes in chemical composition and phase of ale-ale shells through X-Ray Diffraction (XRD) tests with variations in temperature and oven time. Ale-ale shell samples obtained from Oesapa Beach, Kupang, East Nusa Tenggara, were processed through the preparation, heating, and characterization stages using XRD. Testing was carried out at temperatures of 500°C and 700°C with variations in heating time of 2, 4, and 6 hours. The results of the XRD test showed phase changes in samples heated at a temperature of 500°C, where in samples with a time of 6 hours decomposition occurred into CaO with a purity level of 53.4%. At a temperature of 700°C, samples heated for 2 hours showed a purity of 53.3%, and at 6 hours the purity reached 48.2%. All samples showed diffraction peaks indicating 100% calcite content. These results provide an understanding of the changes in the crystal structure and purity of ale-ale shell material, which can be used in biomaterial applications, especially for bone graft materials.